Blood and bone marrow findings in tuberculosis in adults -A cross sectional study - S.R. Dafale; R.Y. Chavan; G.S. Pilli; P.R. Malur; H.B. Bannur; S.S. Sangolli; B.R. Hungund; A.V. Joshi (Al Ameen Medical College, 2012)
Background: Tuberculosis is a major public health problem in India. Hematolgical changes have been studied with variable results. Aims and objectives: The present study was undertaken to know the prevalence of blood and bone marrow changes in tuberculosis. Methods: The peripheral blood and bone marrow changes were evaluated in hundred adult patients with tuberculosis, admitted at District Hospital, Belgaum and KLES Hospital and MRC were. Results: The peripheral blood findings seen were anemia, raised ESR, leukocytosis, neutrophilia, lymphocytosis, eosinophilia, leucopenia, thrombocytosis and thrombocytope-nia. The bone marrow changes seen were hypercellularity , myeloid hyperplasia , erythroid hyperplasia with megaloblastic changes and reactive plasmacytosis. Another interesting finding in bonemarrow was presence of granulomas which were seen in 5% of cases of which 1 case showed positivity for acid fast bacilli on Zeihl -Neelsen stain. Conclusion: The varied hematological findings observed in tuberculosis should prompt us to consider tuberculosis as one of the differential diagnosis in patients with hematological findings.